2021
DOI: 10.1002/ppul.25521
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric long‐COVID: An overlooked phenomenon?

Abstract: Background Long‐COVID is a well‐documented multisystem disease in adults. Far less is known about long‐term sequelae of COVID in children. Here, we report on the occurrence of long‐COVID in Dutch children. Patients and Methods We conducted a national survey asking Dutch pediatricians to share their experiences on long‐COVID in children. We furthermore describe a case series of six children with long‐COVID to explore the clinical features in greater detail. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
3
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 16 publications
9
154
3
5
Order By: Relevance
“…According to a Dutch survey involving 78% of national pediatric departments, 89 children had clinical characteristics attributable to long-covid. Specifically, the main complaints were fatigue, dyspnea and difficulty concentrating [9]. Molteni et al evaluated symptom prevalence, burden and illness duration in 1734 children with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a Dutch survey involving 78% of national pediatric departments, 89 children had clinical characteristics attributable to long-covid. Specifically, the main complaints were fatigue, dyspnea and difficulty concentrating [9]. Molteni et al evaluated symptom prevalence, burden and illness duration in 1734 children with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is known that the course of COVID-19 in children is much less severe than in adults, and more serious complications, such as pneumonia, are less frequent [4][5][6]. However, recent evidence seems to show that long-COVID symptoms also affect younger patients [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although COVID-19 illness is generally milder in children when compared with adults, with low risks of hospitalization and death [ 17 , 18 , 19 ], a small number of children present with a multisystem inflammatory state with an associated mortality rate of 1–2% [ 20 , 21 , 22 ]. Furthermore, evidence is emerging that children may experience long COVID symptoms, similar to adults, which can lead to high morbidity and limitations in daily functioning [ 23 , 24 , 25 ]. In adults, there is clear evidence of post-COVID damage to the lung, heart, kidneys, and brain.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all cases of severe COVID-19 in children are characterizable as MIS-C. A recent study ( 132 ) described demographic and clinical variables associated with MIS-C in comparison with non-MIS-C severe acute COVID-19 in young people in the United States. Efforts to characterize long-term sequelae of SARS-CoV-2 infection in children face the same challenges as in adults, but long-term effects remain a concern in pediatric patients ( 105 , 133 , 134 ), although some early studies have suggested that they may be less of a concern than in adults ( 135 137 ). Research is ongoing into the differences between the pediatric and adult immune responses to SARS-CoV-2, and future research may shed light on the factors that lead to MIS-C; it is also unknown whether the relative advantages of children against severe COVID-19 will remain in the face of current and future variants ( 138 ).…”
Section: Clinical Presentation Of Covid-19mentioning
confidence: 99%